Implementasi Bimbingan Belajar Berdiferensiasi di SD Alam Omah Cendekia Pekalongan Sebagai Model Sekolah Inklusi - Anzilni, Awalia; Latifah, Risalatu; Lizati, Alda Nafila (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
Abstract This article discusses the implementation of differentiated tutoring at SD Alam Omah Scholar Pekalongan as a model of inclusive education. The main focus of the research is to analyze and evaluate how this school integrates a tutoring approach tailored to the individual needs of students, including those with special needs. The research methodology used is a qualitative approach, with data collection through interviews and observation. The data obtained was then analyzed using qualitative descriptive methods through data reduction, data presentation, and drawing conclusions. The research results show the school's commitment to creating an inclusive learning environment, where every student, both with high academic abilities and those who require special attention, receives appropriate support. The differentiated tutoring approach is considered effective in increasing student engagement, facilitating the development of their potential, and overcoming challenges in inclusive education. It is hoped that this article can provide deeper insight into the implementation of a holistic and natural inclusive school model in Indonesia.